Black sun (2005) - Tarn, Gary ([London] : Second Run DVD, 2007)
A look at the life and career of Count Hugues de Montalembert, a French visual artist and filmmaker who was permanently blinded at the age of 35. In the three decades since then, he has turned his efforts to writing & traveling.
film
Keywords: Tarn, Gary; de Montalembert, Hugues